Factors Associated with the Nutritional Status of Chronic Kidney Disease Patients at Depati Hamzah Hospital - Havizah, Havizah; Kusumajaya, Hendra; Hermain, Hermain (Genius Journal, 2026)
Introduction: Chronic Kidney Disease (CKD) sering menyebabkan gangguan status gizi akibat penurunan fungsi ginjal dan efek samping hemodialisis seperti anoreksia dan keluhan gastrointestinal. Berbagai faktor, termasuk usia, jenis kelamin, pendidikan, pekerjaan, dan lama hemodialisis diduga berperan dalam perubahan status gizi pasien. Objective: Impaired nutritional status is a side effect of long-term hemodialysis, as it can cause physiological disturbances, including gastrointestinal problems, that can lead to malnutrition. Several risk factors, such as age, gender, education, occupation, and duration of hemodialysis, are thought to contribute to this nutritional status. This study aims to determine the factors associated with the nutritional status of Chronic Kidney Disease (CKD) patients at Depati Hamzah Pangkalpinang Regional General Hospital in 2025 Method: The research method used is quantitative with a cross-sectional approach. The number of samples is 105 patients selected using quota sampling techniques. Data obtained through questionnaires and medical records, then analyzed univariately and bivariately using the Chi-square test with a confidence level of 95% (α = 0.05). Result: The results of the study showed that there was a significant relationship between age (p = 0.006) having a POR value of 3.307, gender (p = 0.011) having a POR value of 3.025, education (p = 0.005) having a POR value of 3.446, occupation (p = 0.016) having a POR value of 2.896, and duration of hemodialysis (p = 0.001) having a POR value of 3.951 with nutritional status Conclusion: The suggestion from this study is the need for early detection and management of related risk factors, such as regular nutritional status checks, controlling food intake, consulting with nutritionists, and health controls to monitor kidney conditions and detect complications early.